Thermal Management in Hybrid Power Systems Using Cylindrical and Prismatic Battery Cells. Issue 6 (12th April 2016) - He, Fan; Ma, Lin
Abstract : Lithium ion (Li-ion) batteries are promising as both alternative and auxiliary power sources in hybrid and electric vehicles. However, the reliable and efficient operation of the Li-ion batteries depends critically on effective thermal management, due to both the high operational thermal loads and the possible range operational conditions. This work therefore studied the issue of thermal management of battery systems under extreme hot conditions. This study combined both experimental testing and high-fidelity computer fluid dynamics (CFD). Due to the difficulty of conducting experiments under extreme conditions, controlled experiments were first conducted so that CFD models could be validated. The validated CFD models were then applied to study various aspects of thermal management issues in battery systems, with an emphasis on comparing the operation of prismatic and cylindrical batteries under extremely hot environments. The results presented include temperature distribution among cells, pump power required, and different geometrical layouts of the cells. These results are expected to provide insights into the design and optimization of battery systems.